2004
DOI: 10.1002/maco.200303798
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation limited life times of chromia forming ferritic steels

Abstract: Long term, cyclic oxidation studies of three high -Cr, ferritic steels were carried out at 800 8C and 900 8C in air. It was found that with decreasing sample thickness the life time of the mentioned alloys decreases due to breakaway phenomena. This effect is caused by faster exhaustion of the chromium reservoir from the bulk alloy in case of thinner components. The observed life time limits can be predicted with reasonable accuracy by a theoretical model, using oxide growth rate parameters, initial alloy Cr co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 12 publications
3
49
0
Order By: Relevance
“…[26,27] As expected the degree of corrosion rate was less at 650°C, (Figure 14). Both the spinel (exposed 500 h) and the uncoated MS (exposed for 2000 h) samples have a few restricted areas where more extensive oxidation has taken place.…”
Section: Corrosion Resistance Of Coated Substratessupporting
confidence: 75%
“…[26,27] As expected the degree of corrosion rate was less at 650°C, (Figure 14). Both the spinel (exposed 500 h) and the uncoated MS (exposed for 2000 h) samples have a few restricted areas where more extensive oxidation has taken place.…”
Section: Corrosion Resistance Of Coated Substratessupporting
confidence: 75%
“…Both materials were of the type FeCrMn(Ti/La) [5][6][7]. The first material, designated as steel (A), was made of high purity elements, whereas the other steel (B) contained approximately 0.1 wt.-% each of Si and Al [17]. The steel compositions are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…During operation, the Cr from the protective scale evaporates and is replaced by Cr diffusing from the bulk of the alloy. The Cr is consumed until it reaches a concentration of about 16% in the alloy, when break-away oxidation start to occur [21]. On the one hand, it is interesting to reduce interconnect thickness to reduce the cost associated with the interconnect steel, but on the other hand Asensio-Jimenez et al showed that the corrosion rate of interconnect steel increases for thinner plate thickness [22].…”
Section: Introductionmentioning
confidence: 99%